2005
DOI: 10.1007/bf02978215
|View full text |Cite
|
Sign up to set email alerts
|

Antiherpetic activities of flavonoids against herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2)in vitro

Abstract: Flavonoids, a group of low molecular weight phenylbenzopyrones, have various pharmacological properties including antioxidant, anticancer, bactericidal, and anti-inflammatory. We carried out anti-herpetic assays on 18 flavonoids in five classes and a virus-induced cytopathic effect (CPE) inhibitory assay, plaque reduction assay, and yield reduction assay were performed. When flavonoids were applied at various concentrations to Vero cells infected by HSV-1 and 2, most of the flavonoids showed inhibitory effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
167
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(192 citation statements)
references
References 18 publications
8
167
1
5
Order By: Relevance
“…Antiviral activities of numerous flavonoids have been reported. Replication of a number of viruses can be inhibited by baicalein, a member of the flavone subgroup of flavonoids, including herpes simplex viruses 1 and 2 (HSV-1 and HSV-2) and Japanese encephalitis virus (JEV) (Johari et al, 2012;Lyu et al, 2005). In our previous study, we showed that 7-hydroxyflavone and 5,7-dihydroxyflavone substantially inhibited replication of enterovirus 71 in infected cells (Wang et al, 2014a(Wang et al, , 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…Antiviral activities of numerous flavonoids have been reported. Replication of a number of viruses can be inhibited by baicalein, a member of the flavone subgroup of flavonoids, including herpes simplex viruses 1 and 2 (HSV-1 and HSV-2) and Japanese encephalitis virus (JEV) (Johari et al, 2012;Lyu et al, 2005). In our previous study, we showed that 7-hydroxyflavone and 5,7-dihydroxyflavone substantially inhibited replication of enterovirus 71 in infected cells (Wang et al, 2014a(Wang et al, , 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…4) had the highest anti-HSV activity, reducing the viral titer by 2log 10 or more (38). This was confirmed by Lyu et al, who additionally demonstrated that the two substances had high anti-HSV in vitro activity, and that flavonols had higher activity than flavones (39).…”
Section: Natural Products With Anti-herpes Simplex Virus Activitymentioning
confidence: 69%
“…Також флавоноїди виявляють протизапаль-ний, антибіотикоподібний потенціал: діючи як антимікробні агенти, пригнічують функціону-вання патогенних мікроорганізмів [12,15].…”
Section: вступunclassified